Kounis syndrome: a paradoxal non-ST elevation myocardial infarction case after triamcinolone treatment for dermatitis - Yilmaz, Mucahid; Korkmaz, Hasan (Turkish Soc Cardiology, 2018)
Kounis syndrome is defined as the clinical development of acute coronary syndrome caused by the activation of inflammatory cells due to an allergy, hypersensitivity, anaphylaxis, or anaphylactic reaction. Corticosteroids that are used in the treatment of many inflammatory conditions may paradoxically cause allergic reactions and even anaphylaxis. This article is a description of the case of a 52-yearold female patient who had a non-ST elevation myocardial infarction after the administration of triamcinolone that was relieved with antihistaminic treatment. The patient had been diagnosed with dermatitis at another medical center and injected with 40 mg/mL (intramuscular [IM]) of triamcinolone acetonide and developed chest pain 15 minutes after the first dose. Despite a normal physical examination and echocardiogram, laboratory tests revealed troponin positivity and an inferolateral ST depression was present on an electrocardiogram (ECG). The ECG findings and clinical symptoms resolved completely after conservative anti-ischemic treatment and antihistaminic therapy (pheniramine maleate 45.5 mg/2 mL, Avil ampoule, IV, Sanofi-Aventis, Paris, France) and coronary angiography evaluation of the arteries was normal. The heart, and in particular the coronary arteries, are among the organs that are most damaged during hypersensitivity reactions and anaphylaxis. Although Kounis syndrome is not a rare condition, few cases have been reported in clinical practice. The failure to recognize Kounis syndrome due to inadequately defined cases may lead to unwanted medical results. Kounis syndrome should be kept in mind in order to make a rapid and accurate diagnosis.
Keywords: Management; Histamine; Angina